Contingencies in Victim-Offender Overlap: Do Timing and Number of Arrests Matter? - Kopf, Samantha (Victims & offenders, 2025)
Scholars have studied the victim-offender overlap within the context of offending; however, only a handful of these studies have explored the link between arrest and violent victimization. This lack of attention to arrest experiences, specifically to timing of arrest, represents a large gap in the life course literature as we know that adverse experiences in adolescence, such as arrest, tend to carry more weight than adverse experiences that occur in adulthood. Using four waves of data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), this study examines the age-graded association of arrest experiences with violent victimization, net of other important theoretical mechanisms (i.e. offending). Negative binomial regression models reveal that, net of offending, arrest experiences are a significant predictor of violent victimization. Interactions show that offending, victimization, and arrest are interdependent, with each influencing and amplifying the others through reciprocal processes. Findings highlight that age at first arrest operates as a turning point in predicting one’s victimization experiences, net of offending.